Alteration and Mineralisation of Sulphide Deposits in The Lipukasi Area, Barru Regency, South Sulawesi Province - Wakila, Muhamad Hardin; Harwan; Thamsi, Alam Budiman; Aulia, Rizky Nurul; Aulia, Rieska Dewi (Candela Edutech Indonesia, 2025)
In the Lipukasi area, Barru Regency, South Sulawesi Province, sulphide deposits and complex alteration processes have been discovered. However, information regarding the alteration and mineralisation that has developed in this area is not yet available, so further research is needed to identify the types of alteration and mineralisation present in the Lipukasi area, Barru Regency, South Sulawesi Province. The purpose of this study was to determine the type of hydrothermal alteration and mineralisation that developed in the study area. The analytical method used in this research first carried out megaskopis analysis to determine the physical properties of the sample. After that, laboratory analyses of mineragraphy and X-Ray Diffraction (XRD) were carried out. The results of megascopic analysis of the two research samples are an igneous rock with a fresh grey colour, a weathered yellowish-brown colour, a massive structure, an intermediate rock type, a crystalline texture, namely holocrystalline, a granularity, namely phaneroparabolic, a relationship, namely equigranular, and a crystal shape, namely euhedral. The minerals found from the results of mineralographic and XRD analysis are Hematite, mafic mineral, goethite, silica mineral, sulphide mineral (galena, chalcopyrite, pyrite, covellite), quartz, and kaolinite. So it can be concluded the minerals found in the study area are hematite (Fe₂O₃), mafic minerals, silica minerals, goethite (FeO₂H), galena (PbS), covellite (CuS), chalcopyrite (CuFeS₂), pyrite (FeS₂), kaolinite and quartz (SiO₂). Based on the indicated mineral composition, the type of alteration that developed in the study area is propylitic